A Novel Photocatalyst with Ferromagnetic Core Used for the Treatment of Olive Oil Mill Effluents from Two-Phase Production Process - Javier Miguel Ochando-Pulido; Gassan Hodaifa; María Dolores Víctor-Ortega; Antonio Martínez-Ferez (The Scientific World Journal)
Photocatalytic degradation of olive oil mill wastewater from two-phase continuous centrifugation process was studied. A novel photocatalyst with ferromagnetic properties was characterized and investigated. The degradation capacity of the photocatalytic process of olive oil washing wastewater (OMW) and mixture of olives and olive oil (1 v/v) washing wastewaters (MOMW) was demonstrated. At lab-scale, the %COD removal and residence time (τ) for MOMW and OMW were 58.4% (τ=2 h) and 21.4% (τ=3 h), respectively. On the other hand, at pilot scale, 23.4% CODremoval, 19.2% total phenolsremoval, and 28.1% total suspended solidsremoval were registered at the end of the UV/TiO2 process for OMW, whereas 58.3% CODremoval, 27.5% total phenolsremoval, and 25.0% total suspended solidsremoval for MOMW. Also, before the UV/TiO2 reaction, a pH-T flocculation operation as pretreatment was realized. The overall efficiency of the treatment process for MOMW was up to 91% of CODremoval, in contrast with 33.2% of CODremoval for OMW.